Atypical features of mixed epithelial and stromal tumour of kidney: a case report with histopathology correlation - Se To, Wei Li; Halim Lim, Aidi Aswadi; Che Mohamed , Siti Kamariah; Kamarulzaman, Mohd Nazli; Ahmad Affandi, Khairunisa (IIUM Journal of Orofacial and Health Sciences, 2026)
Adult cystic nephroma and mixed epithelial stromal tumours (MEST) are classified under the mixed epithelial and stromal tumour (MEST) family, which is a part of the 2016 World Health Organisation (WHO) renal tumour classification. They are rare, benign tumours which have similar imaging appearance as certain types of renal carcinoma. Hence, it is often regarded as malignant pre-operatively and histopathologically confirmed to be benign. We present a case of a 66-year-old lady who complains of gradual abdominal distension for 9 months, associated with loss of appetite, loss of weight and early satiety. Other than clinical findings that point towards ascites, the rest of her physical examination was unremarkable. Blood investigations including tumour markers were normal. Abdominal ultrasound and computed tomography (CT) showed a huge unilocular intra-abdominal cystic mass with enhancing solid component attached to the right kidney which was exerting significant mass effect to the surrounding structures. The patient developed impending abdominal compartment syndrome and underwent right nephrectomy with tumour excision. The final histopathological diagnosis revealed mixed epithelial and stromal tumour (MEST). The patient recovered well. Mixed epithelial stromal tumour (MEST) is a rare clinical entity. Ultrasound and CT imaging are the usual investigating modalities. Histopathological correlation is needed to reach the diagnosis. This case has an unusual and different radiological imaging appearance when compared to past literature and contributes an additional case to our collective knowledge of these lesions.